(untitled) (Research, Society and Development, 2020)
The present study aimed to analyze the presence of Pressure Injury (PI) in hospitalized patients, observing the main associated comorbidities. This is a retrospective document analysis, with an analytical observational profile, of a quantitative and transversal character. The research was carried out in a highly complex hospital in the public network, located in the state of Paraíba and was carried out through a careful analysis of 884 medical records of patients admitted from January to December 2019, including those who had at least an PI during your hospital stay. Information such as sociodemographic profile, age, sex, clinical history of the patient and associated diseases were evaluated, in addition to the Braden scale score to identify the risk of developing the lesion. The sample consisted of 85 patients, most of whom (83.5%) were over 65 years of age, 47 (55.29%) were female and 38 (44.71%) were male. An incidence of 11.5% of the presence of PI was observed in patients, characterized as a number to be taken into account, since it is a complication classified as preventable in most cases, and it is also known underreporting as it is considered a medical malpractice problem. Diabetes Mellitus (DM) and Systemic Arterial Hypertension (SAH) were identified as the main associated comorbidities, and of the patients who developed PI, 10 (11.8%) had DM, 21 (24.7%) had SAH and 33 (38.8%) had both diseases, with implications for wound healing and worsening. Therefore, it is relevant to emphasize the importance of systematic monitoring of the patient, in order to verify the existing comorbidities and the risks of the occurrence of the injury, in order to maximize the preventive care, providing a better hospital stay for the patient and avoiding high treatment costs.